The design of video games in the implementation of Malay language learning among foreign students in an institution of higher learning - Rosman, Fuziah; Alias, Norlidah; Abd rahman, Mohd Nazri; Dewitt, Dorothy (Universiti Malaya, 2015)
This study aims at reviewing the curriculum design by including video games in the implementation of the Malay language course at an Institute of Higher Learning. The objective of this study is to obtain expert opinion on the expected manner of implementation of video games in learning the Malay language. The Fuzzy Delphi technique (FDM) is used to obtain the consensus among 30 selected experts from various fields and backgrounds using an instrument specifically designed for the purpose. The instrument consists of six sub items. The findings show that experts reached a consensus and agreed that the curriculum design based video games could be tailored to the learning of the Malay language among foreign students (defuzzified value: 0.680). Overall, the experts had consensus and strongly agreed that video games have potential in implementing Malay language learning among foreign students at a university. The impact from the expert consensus was that a decision was made for a new framework for curriculum design based on the potential of video games as a medium of instruction for scaffolding learning of Malay language among foreign students at a selected university. Thus, this study suggests the implementation of new education policies among stakeholders particularly at the Department of Higher Education and Ministry of Education (MOE) to highlight the possibility of using video games as a teaching tool for all universities nationwide. The Curriculum Development Centre at the Centre for Language and other faculties in all universities should view the development of this technology to enable application of a more interesting, interactive and motivating language learning process as a medium of learning the Malay language among foreign students.